2011
DOI: 10.1176/ps.62.5.pss6205_0541
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Peer Support in Reducing Readmissions of Persons With Multiple Psychiatric Hospitalizations

Abstract: Despite the study's limitations, findings suggest that use of peer mentors is a promising intervention for reducing recurrent psychiatric hospitalizations for patients at risk of readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
146
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(156 citation statements)
references
References 13 publications
9
146
0
1
Order By: Relevance
“…There has been a growing movement in psychological practice toward the inclusion of peer support approaches, whereby individuals with experience of mental health problems provide support for people with similar experiences [49]. The potential value of peer support has been widely discussed in the literature and is associated with improved functioning, empowerment, and confidence [49], reductions in hospital admissions [50], and increased social networks and wellbeing [51]. The notion that social media could provide an accessible avenue for peer support is not new necessarily.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a growing movement in psychological practice toward the inclusion of peer support approaches, whereby individuals with experience of mental health problems provide support for people with similar experiences [49]. The potential value of peer support has been widely discussed in the literature and is associated with improved functioning, empowerment, and confidence [49], reductions in hospital admissions [50], and increased social networks and wellbeing [51]. The notion that social media could provide an accessible avenue for peer support is not new necessarily.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, findings from these four RCTs showed that professional and peer mentor services were not significantly different yet these findings have to be interpreted conservatively because they fundamentally represent support of a null hypothesis (no difference between peer and professional case managers). More recently, Sledge et al (2011) reported on an intervention that enrolled people with serious mental illness who had two or more psychiatric hospitalizations during the past 18 months. Participants were randomized to weekly support of peer mentors or aftercare as usual.…”
Section: Integrated Care and Patient Navigatorsmentioning
confidence: 99%
“…Prior studies conducted in Western countries have demonstrated that services provided by multidisciplinary outreach teams who had CPs as team members were able to accomplish a variety of improvements in client outcomes. These included: an ability to quickly create treatment relationships, improve the quality of services, shorten periods of hospitalization, reduce re-hospitalization, lengthen the time spent living in the community, promote the recovery of the users of these services, and improve quality of life [711]. It has also been demonstrated that having CPs on multidisciplinary teams promoted the recovery of CPs.…”
Section: Introductionmentioning
confidence: 99%